Introduction to Academic Writing - Oshima, Alice, Hogue, Ann (Addison Wesley Longman, 1997)
The intermediate level of the Longman Academic Wriitng series, helps students master the standard organizational patterns for paragraphs and essays. The text's approach integrates the study of rhetorical patterns and writing process with extensive practice in grammar, mechanics, and sentence structure.